Aesthetically potent environments : an exploration of technology, meaning and embodied interaction : a thesis presented in partial fulfillment of the requirements for the postgraduate degree of Master of Fine Arts at Massey University, Wellington campus, New Zealand - Bennewith, Christopher David; Bennewith, Christopher David (Massey University, 2011)
When an artistic or aesthetic experience no longer relies on an audience to “passively” consume it, but rather entices the viewer to become an active participant in the artwork, how is the perception of the work and, subsequently, the audience affected? How does the audience encounter and make meaningful these types of experience? Squidsoup have, for the past 10 years, been exploring these questions through their practice--based research. Their interactive artworks engage the audience as part of a sociotechnical network, as both a component of the overall aesthetic experience and as a catalyst for compositional change within the artwork. In our everyday lives we experience the world as a physical and social space. In order to elicit the greatest action and interaction from an audience Squidsoup attempt to make the intangible tangible, and create works where social interaction between the participants is encouraged. As computing becomes more ubiquitous, moves away from the desktop and starts to occupy the “physical” spaces around us, the ways in which people engage with technology, and each other, will change. Squidsoup’s most recent work – Ocean of Light: Surface – seeks to explore the interrelationship between people, technology and space and how this could manifest as a potential aesthetic experience. Ocean of Light: Surface looks to bring digital interactive artworks into the physical and spatial realm of the audience in order to explore the effect this has on the way they interact with, and consequently understand, the work. This research will draw on my current and previous practice as part of Squidsoup and locate it within a wider historic, artistic and theoretical context. The thesis will detail the development of the concepts underpinning our artistic practice by relating case study examples to historic and contemporary art practice and relevant theoretical literature. Ocean of Light: Surface will be the physical and practical manifestation of this research embodied within an artwork.
Keywords: Audience participation; Interactive art; Art installations